The performance of CO2/N2 separation on P84/NCC-based tubular carbon membrane under different carbonization conditions - Norazlianie, Sazali; Mohd Syafiq, Sharip; Haziqatulhanis, Ibrahim; Wan Norharyati, Wan Salleh; Nur Izwanne, Mahyon; K., Kadirgama; Zawati, Harun; Norsuhailizah, Sazali (Penerbit UTM Press, 2019)
In this study, the influence of carbonization environment on the performance of Tubular Carbon Membrane (TCMs) was explored. P84 co-polyimide/Nanocrystalline cellulose-based TCMs were synthesized by dip-coating technique. The permeation properties of TCMs were determined by employing pure gas of CO2 and N2. Heat treatment processes were carried out under different environment (Argon, Nitrogen, and Helium) with the flow rate of 200 ml/min to boost the membrane’s performance. The carbonization process was performed at a consistent carbonization temperature of 800oC under heating rate of 3oC/min. Carbonization under Argon environment was found to be the best condition for PI/NCC-based TCMs preparation with the permeance of 3.22±3.21and 213.56±2.17 GPU for N2, and CO2 gases, respectively. This membrane exhibited the uppermost CO2/N2 selectivity of 66.32±2.18. TCMs prepared under Ar environment experienced less weight loss while exhibiting highest CO2/N2 selectivity as compared to those prepared under He and N2 environment.